Sustainable Red Mud Conversion to ZSM-5 - Tehubijuluw, Hellna; Subagyo, Riki; Nugraha, Reva Edra; Prasetyoko, Didik; Kusumawati, Yuly; Jalil, Aishah Abdul; Bahruji, Hasliza (Trends in Sciences, 2025)
Red mud (RM), a highly alkaline industrial byproduct of alumina production, poses significant environmental challenges due to its massive accumulation and hazardous composition. This study addresses these issues by developing a sustainable method to convert RM into high-performance mesoporous ZSM-5 zeolite. A dual-hydrothermal synthesis approach was employed, combining alkali fusion and hydrothermal treatment with cetyltrimethylammonium bromide (CTAB) as a structure-directing agent to enhance mesoporosity. Comprehensive characterization was performed to confirm the structural and textural properties of the synthesized ZSM-5. X-ray diffraction (XRD) analysis confirmed the successful formation of the highly crystalline MFI zeolite framework, while Fourier-transform infrared spectroscopy (FTIR) validated the incorporation of aluminosilicate species. Nitrogen adsorption-desorption analysis revealed a significant enhancement in surface area (734 m²/g) and dual porosity, with micropores (1.18 nm) and mesopores (2.79 nm) present. Scanning electron microscopy (SEM) highlighted the morphological transformation from aggregated particles in RM to well-defined cubic structures characteristic of ZSM-5. The synthesized material exhibited promising properties for adsorption applications, particularly in addressing environmental challenges such as wastewater treatment. This study demonstrates a scalable and eco-friendly approach to valorizing industrial waste, contributing to sustainable material development and the circular economy. HIGHLIGHTS A sustainable dual-hydrothermal synthesis method was employed to transform red mud (RM) into mesoporous ZSM-5. The synthesis significantly enhanced the material's structural and textural properties, achieving a BET surface area of 734 m²/g. XRD analysis confirmed the successful formation of the highly crystalline MFI zeolite framework. FTIR spectroscopy validated the incorporation of silica and alumina into the ZSM-5 structure, with characteristic T-O-T vibration. GRAPHICAL ABSTRACT